2015
DOI: 10.1002/etc.3010
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistency in the analysis of morphological deformities in chironomidae (Insecta: Diptera) larvae

Abstract: The incidence of morphological deformities of chironomid larvae as an indicator of sediment toxicity has been studied for decades. However, standards for deformity analysis are lacking. The authors evaluated whether 25 experts diagnosed larval deformities in a similar manner. Based on high-quality digital images, the experts rated 211 menta of Chironomus spp. larvae as normal or deformed. The larvae were from a site with polluted sediments or from a reference site. The authors revealed this to a random half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…In this regard, some studies based on ecotoxicological laboratory experiments queried the relationship between chironomid deformities and toxicity assessment in freshwater ecosystems [24,49,[72][73][74][75][76]. However, the high variability of those experimental results can be influenced by different variables, such as: (i) the endpoint used (mentum, mandibles, pectin epipharyngis); (ii) the deformity types considered; (iii) the larval instars used in the experiment; (iv) the type of cultures used which often cause a high incidence of deformities in the control test; (v) the exposure time of the larvae to the contaminants; and (vi) the type of contaminant mixture used in the test.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies based on ecotoxicological laboratory experiments queried the relationship between chironomid deformities and toxicity assessment in freshwater ecosystems [24,49,[72][73][74][75][76]. However, the high variability of those experimental results can be influenced by different variables, such as: (i) the endpoint used (mentum, mandibles, pectin epipharyngis); (ii) the deformity types considered; (iii) the larval instars used in the experiment; (iv) the type of cultures used which often cause a high incidence of deformities in the control test; (v) the exposure time of the larvae to the contaminants; and (vi) the type of contaminant mixture used in the test.…”
Section: Discussionmentioning
confidence: 99%
“…Chironomid mentum deformity incidence (DI) did not differ among the sediments, and was in all exposures within the range suggested to represent a background incidence of 2.8 % to less than 8.0 % (Dickman et al 1992;Vermeulen 1995;Salmelin et al 2015) found in minimally disturbed sites in the field. DI seemed not to be related to the chironomid growth, which was reduced in 1A, 2B and 4B sediments, but not in 3A sediment, where the DI was the highest.…”
Section: Discussionmentioning
confidence: 95%
“…Only mentum deformities were considered. Missing or additional teeth, and Köhn gaps were counted as deformities, and to avoid a preconception bias, deformity analysis was conducted blind (Salmelin et al 2015).…”
Section: Exposure Setup and Measured Responses Of Chironomus Ripariusmentioning
confidence: 99%
“…gyakran használják a szennyeződések és a víz alacsony oxigéntartalmának indikátorául (Lenat 1993, Michailova et al 2015. A környezeti stressz vizsgálatára jól használhatóak a vízben élő légylárvák fejtokjának morfológiai elváltozásai (Warwick 1991, Salmelin et al 2015. Bár az az általános vélekedés, hogy a legtöbb vízi Diptera toleráns a környezeti hatásokkal szemben, de bizonyos csoportok, például a Blephariceridae, Thaumaleidae családok fajai rendkívül érzékenyek a környezeti zavarásokra (Lenat 1993, Searher & Wagner 2002.…”
Section: Kétszárnyúak Mint Természetvédelmi Bioindikátorokunclassified